Magnetic Anomaly Model Interpretation of Geothermal Area in Air Putih Region, Lebong District, Bengkulu Province - Jessica Agnes Soroinama Gea; Refrizon; Halauddin; Eko Heru Purwanto; Widya Kurnia Sari; Juni Putri Rizki (Universitas Negeri Semarang, 2024)
Lebong Regency is located in the Sumatra Fault Zone, a relatively long dextral shear fault, causing unique structural and morphological changes around the fault zone. The Air Putih area, Lebong Regency, has geothermal manifestations in the form of hot springs that gush and flow from river banks and cliffs. In determining the subsurface structure model, magnetic anomalies were interpreted from direct measurements using two sets of Proton Precession Magnetometers (PPM) as the base and rover. The magnetic method was used to identify the subsurface structures displayed in a 2D model. The results of magnetic anomaly mapping in the study area show that 2D modelling can provide an overview of objects or rocks that cause anomalies at the study site. Based on subsurface modeling at the research site, four incisions were made, namely incisions A-A’ with a susceptibility contrast value of 0.516042 SI with hematite mineral type; in incisions B-B', it is suspected that is a mineral, namely gneiss with a susceptibility value of 0.164160 SI; incision C-C' has a susceptibility value of 0.172010 SI with gneiss rock type; and incision D-D' has a susceptibility value of 0.060604 SI, which is suspected to be a pyrite mineral. The rock types in the study area are mainly thought to be gneiss igneous rocks and the magnetic minerals quartz, pyrite, and calcite, which have different susceptibility values.